(untitled) (Nepal Journal of Epidemiology, 2013)
The aims of pharmacovigilance are early recognition of previously unknown adverse drug reactions (ADRs), recognition of changes in frequency of known ADRs, identification of risk factors and mechanism of ADRs, quantitative analysis of benefit/risk ratio and dissemination of safety information for rational drug prescribing and regulation. The pharmacovigilance programme in Nepal is a recent development. The Department of Drug Administration (DDA) took the initiative to set up a pharmacovigilance program in 2002; however, it was initiated systematically only after two years. DDA acts as the National Pharmacovigilance Centre (NPC). It collects ADR case reports from the Regional Pharmacovigilance Centre (RPC). Currently there are six RPCs operating in the country. The current reporting trends suggest high under-reporting of suspected ADRs. This paper is a review of those studies which are focused on pharmacovigilance and healthcare professionals’ perspectives on ADR reporting in Nepal. It also recommends the possible ways to improve the ADR reporting based on the context of Nepal. DOI: http://dx.doi.org/10.3126/nje.v3i1.8286 Nepal Journal of Epidemiology 2013;3 (1): 230-235